Detecting The Expected Rate of Return Volatility of Financing Instruments of Indonesian Islamic Banking through GARCH Modeling (Generalized Autoregressive Conditional Heteroscedasticity) - Nurul Huda; Amrin Barata (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objective - Islamic banks are banks which its activities, both fund raising and funds distribution are on the basis of Islamic principles, namely buying and selling and profit sharing. Islamic banking is aimed at supporting the implementation of national development in order to improve justice, togetherness, and equitable distribution of welfare. In pursuit of supporting the implementation of national development, Islamic banking often faced stability problems of financing instruments being operated. In this case, it is measured by the gap between the actual rate of return and the expected rate of return. The individual actual RoR of this instrument will generate an expected rate of return. This raises the gap or difference between the actual rate of return and the expected rate of return of individual instruments, which in this case is called the abnormal rate of return. The stability of abnormal rate of return of individual instruments is certainly influenced by the stability of the expected rate of return. Expected rate of return has a volatility or fluctuation levels for each financing instrument. It is also a key element or material basis for the establishment of a variance of individual instruments. Variance in this case indicates the level of uncertainty of the rate of return. Individual variance is the origin of the instrument base for variance in the portfolio finance that further a portfolio analysis. So, this paper is going to analyze the level of expected RoR volatility as an initial step to see and predict the stability of the fluctuations in the rate of return of Indonesian Islamic financing instruments.Methods – Probability of Occurence, Expected Rate of Return (RoR) and GARCH (Generalized Autoregressive Conditional Heteroscedasticity).Results - The expected RoR volatility of the murabaha and istishna financing instruments tend to be more volatile than expected RoR volatility of musharaka and qardh financing instruments.Conclusions – The uncertainity of Musharaka and qardh financing instruments tend to be more stable than other Islamic financing instruments.